2022
DOI: 10.3390/pr10050998
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Experimental Validation of Contact Parameters in a Discrete Element Model for Tobacco Strips

Abstract: To study the contact parameters of the tobacco strips during redrying, in this study, the funnel stacking test is used to determine the stacking angle, and the discrete element method is used to simulate the formation process of the stacking angle, to calibrate and verify the physical and contact parameters of tobacco strips. The Placket–Burman test was used to screen out the parameters that had significant effects on the stacking angle. The regression response surface model between the stacking angle and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…This study revealed that µ r,pp , µ s,pp and µ s,ps exert significant effects on the stacking angle, which is consistent with previous research works' conclusions [28,30]. This might occur because walnuts make autorotation to respond to the coupling effect between the frictional force and gravity during cylinder lifting.…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed that µ r,pp , µ s,pp and µ s,ps exert significant effects on the stacking angle, which is consistent with previous research works' conclusions [28,30]. This might occur because walnuts make autorotation to respond to the coupling effect between the frictional force and gravity during cylinder lifting.…”
Section: Discussionsupporting
confidence: 90%
“…The experimental material used was Yuxi tobacco strips with a density of 280 kg/m 3 [8], which were sampled and placed in a sealed bag. The initial moisture content of heaped tobacco strips was calculated to be 8.5% by using the weight method [30] after drying at 105 °C.…”
Section: Experimental Verification Of the Moisture Contentmentioning
confidence: 99%
“…The experimental material used was Yuxi tobacco strips with a density of 280 kg/m 3 [8], which were sampled and placed in a sealed bag. The initial moisture content of heaped tobacco strips was calculated to be 8.5% by using the weight method [30] after drying at 105 • C. The experimental equipment includes a scaled-down rewet box (0.39 m × 0.44 m × 0.7 m), some net baskets (0.08 m × 0.08 m × 0.1 m), a temperature-controlled steamer, an electronic balance, a ruler, and a temperature and relative humidity meter.…”
Section: Experimental Verification Of the Moisture Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…accurately and rapidly acquired the DEM model parameters of pig manure organic manure grains after treatment with Hermetia illucens, and with the repose angle as the response value and on basis of response surface method (RSM), calibrated the pig manure organic manure simulation parameters at the water content of 43.6% after the treatment with Hermetia illucens, providing a theoretical basis for fertilization machine screening [15]. As for calibration of other parameters, Wei Jiang et al simulated the repose angle of tobacco through DEM, and built a regression RSM model between the repose angle (as the response value) and contact parameters [16]. Jiahui Ren et al measured the basic physical parameters and repose angle of sugar cane leaves through physical experiments, and conducted DEM simulation using the repose angle as the response value, which offered reference for parameter calibration of the strip-and blade-shaped straw materials [17].…”
Section: Introductionmentioning
confidence: 99%